Melt processability, characterization, and antibacterial activity of compression-molded green composite sheets made of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) reinforced with coconut fibers impregnated with oregano essential oil. (September 2018) - Torres-Giner, S.; Hilliou, L.; Melendez-Rodriguez, B.; Figueroa-Lopez, K.J.; Madalena, D.; Cabedo, L.; Covas, J.A.; Vicente, A.A.; Lagaron, J.M.
Highlights: Optimal incorporation of CFs into PHBV was achieved by melt compounding at 150 rpm. Green composite sheets with enhanced physical performance were produced. CFs were also impregnated with OEO to develop a novel antibacterial filler. Sheets with OEO-containing CFs showed bacteriostatic effect against G+ S. aureus. Relevant applications in the active food packaging field are foreseen. Abstract: New packaging materials based on green composite sheets consisting of poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) and coconut fibers (CFs) were obtained by twin-screw extrusion (TSE) followed by compression molding. The effect of varying the CF weight content, i.e. 1, 3, 5, and 10 wt.-%, and the screw speed during melt processing, i.e. 75, 150, and 225 rpm, on both the aspect ratio and dispersion of the fibers was analyzed and related to the properties of the compression-molded sheets. Finally, the CFs were impregnated with oregano essential oil (OEO) by an innovative spray coating methodology and then incorporated into PHBV at the optimal processing conditions. The functionalized green composite sheets presented bacteriostatic effect against Staphylococcus aureus from fiber contents as low as 3 wt.-%. Therefore, the here-prepared CFs can be successfully applied as natural vehicles to entrap extracts and develop green composites of high interest in active food packaging to provide protection and shelf life extension.